Twenty‐Four‐Hour Electrocardiographic Monitoring for Assessment of Cardiac Arrhythmias in Healthy and Hospitalized Goats - Alyssa Sullivan; Darcy B. Adin; Sara B. Speziok; Dana Haimovitz; Todd C. Holbrook; Daniela Luethy (Journal of Veterinary Internal Medicine)
ABSTRACT Background Continuous 24‐h electrocardiographic (ECG) recording is a well‐established method for the detection of intermittent arrhythmias in veterinary medicine. The clinical utility of 24‐h ECG for the detection of intermittent arrhythmias in hospitalized goats has not been reported. Hypothesis/Objectives (1) Determine the clinical feasibility of continuous 24‐h ECG monitoring in goats; (2) Report the frequency of ventricular arrhythmias in healthy and hospitalized medically ill goats. Animals Eleven healthy goats, 20 hospitalized medically ill goats. Methods Prospective clinical study. Continuous 24‐h ECG recordings were performed. Electrocardiograms were analyzed for rhythm diagnosis. The number of ventricular premature depolarizations (VPD) was compared between groups using the Wilcoxon rank sum test. Results The ECG monitors were well‐tolerated in 30/31 goats, with no adverse effects. Twenty‐eight recordings were of sufficient quality for analysis with a median readable time of 23 h (range, 15–24 h). Eleven goats had ventricular arrhythmias (4 healthy, 7 medically ill), consisting of single VPDs only in 7 goats (3 healthy, 4 medically ill), VPDs and ventricular couplets in 4 goats (1 healthy, 3 medically ill), and ventricular rhythm consistent with accelerated idioventricular rhythm (AIVR) or ventricular tachycardia in 2 goats (2 medically ill). A significant difference in the number of VPDs in healthy goats (median, 0; range, 0–9) and medically ill goats was not identified (median, 0; range, 0–201; p = 0.66), but a larger sample size is required. Conclusion and Clinical Importance Most goats tolerated 24‐h ECG monitoring well, although a few recordings were of poor quality. Ventricular arrhythmias were seen in healthy and medically ill goats.